The Brain: A New Organ for the Metabolic Actions of SIRT1 - Al Massadi, O.; Quiñones, M.; Lear, P.; Dieguez, C.; Nogueiras, R. (Hormone and Metabolic Research, 2013)
The sirtuins are a family of highly conserved nicotine adenine dinucleotide (NAD+)-dependent deacetylases that act as cellular sensors to detect energy availability and regulate metabolic processes. Sirtuin 1 (SIRT1) is one of the family members that is activated in response to caloric restriction, acting on multiple targets in a wide range of tissues. Recent studies have shown that SIRT1 controls glucose and lipid metabolism in both liver and muscle, promotes fat mobilization, stimulates remodeling of white to brown fat, controls insulin secretion in the pancreas, and senses nutrient availability in the hypothalamus. SIRT1 is located in several areas of the brain and its central metabolic actions have attracted much attention in the last decade. In this short review, we summarize the main actions and molecular pathways triggered by SIRT1 that control feeding behavior, energy expenditure, glucose metabolism, and insulin sensitivity, with an emphasis on the emerging role of SIRT1 in the brain.
Keywords: insulin sensitivity; adipose tissue; impaired glucose tolerance; obesity